2007
DOI: 10.5194/cp-3-15-2007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical reconstructions of the Northern Hemisphere ice sheets through the last glacial-interglacial cycle

Abstract: Abstract.A 3-dimensional thermo-mechanical ice-sheet model is used to simulate the evolution of the Northern Hemisphere ice sheets through the last glacial-interglacial cycle. The ice-sheet model is forced by the results from six different atmospheric general circulation models (AGCMs). The climate evolution over the period under study is reconstructed using two climate equilibrium simulations performed for the Last Glacial Maximum (LGM) and for the present-day periods and an interpolation through time between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
134
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 69 publications
8
134
0
Order By: Relevance
“…Numerical ice sheet modeling could improve the understanding of this period but most studies focus on the primary inception regions over North America and western Siberia (Marshall and Clarke, 1999;Zweck and Huybrechts, 2005;Calov et al, 2005a;Kubatzki et al, 2006;Charbit et al, 2007;Peyaud et al, 2007). This is probably due to the lack of constraints on timing and extent of ice from data, but also because the steep Scandinavian topography and variable climate are a challenge for the realistic representation of glaciers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical ice sheet modeling could improve the understanding of this period but most studies focus on the primary inception regions over North America and western Siberia (Marshall and Clarke, 1999;Zweck and Huybrechts, 2005;Calov et al, 2005a;Kubatzki et al, 2006;Charbit et al, 2007;Peyaud et al, 2007). This is probably due to the lack of constraints on timing and extent of ice from data, but also because the steep Scandinavian topography and variable climate are a challenge for the realistic representation of glaciers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the geographical extents of the LGM ice sheets are well constrained, it is still uncertain how the ice sheets arrived at the observed extents (Dyke et al, 2002;Kleman et al, 2010). Modelling efforts of the last glacial cycle reveal different results of the ice-sheet extent at LGM (Tarasov and Peltier, 1997;Charbit et al, 2007;Bonelli et al, 2009). Typically, the models predict too much ice on Alaska or they are unable to capture the increased equatorward extent over eastern North America.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, features associated with ice-sheet dynamics and the atmospheric state remain sources of uncertainty. The uncertainty associated with the atmospheric state was illustrated in Charbit et al (2007), who simulated the evolution of the ice sheets through the last glacial cycle using anomalies of temperature and precipitation computed by six different atmospheric general circulation models (AGCMs). They found that the spatial distributions and shapes of the Northern Hemisphere ice sheets at LGM were sensitive to the employed atmospheric model.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difference of resolution between the atmospheric and the ice-sheet models, temperature is vertically corrected using a linear vertical gradient of 6 K km −1 . Precipitation is also vertically corrected using an exponential function of the temperature (Charbit et al, 2002(Charbit et al, , 2007. Snowfall is recalculated using the downscaled precipitation and temperature because the more detailed topography of GRISLI allows snowfall when LMDZ5 provides only liquid precipitation.…”
Section: In Case Of No Initial Fennoscandian Ice Sheetmentioning
confidence: 99%